Genetic mixed-stock analysis disentangles spatial and temporal variation in composition of the West Greenland Atlantic Salmon fishery. (4th May 2016) - Bradbury, Ian R.; Hamilton, Lorraine C.; Sheehan, Timothy F.; Chaput, Gerald; Robertson, Martha J.; Dempson, J. Brian; Reddin, David; Morris, Vicki; King, Timothy; Bernatchez, Louis
Abstract: The West Greenland Atlantic Salmon ( Salmo salar ) fishery represents the largest remaining mixed-stock fishery for Atlantic Salmon in the Northwest Atlantic and targets multi-sea-winter (MSW) salmon from throughout North America and Europe. We evaluated stock composition of salmon harvested in the waters off West Greenland ( n = 5684 individuals) using genetic mixture analysis and individual assignment to inform conservation of North American populations, many of which are failing to meet management targets. Regional contributions to this fishery were estimated using 2169 individuals sampled throughout the fishery between 2011 and 2014. Of these, 22% were identified as European in origin. Major North American contributions were detected from Labrador (∼20%), the Southern Gulf/Cape Breton (29%), and the Gaspe Peninsula (29%). Minor contributions (∼5%) were detected from Newfoundland, Ungava, and Quebec regions. Region-specific catches were extrapolated using estimates of composition and fishery catch logs and harvests ranged from 300 to 600 and 2000 to 3000 individuals for minor and major constituents, respectively. To evaluate the temporal stability of the observed fishery composition, we extended the temporal coverage through the inclusion of previously published data (1995 – 2006, n = 3095) and data from archived scales (1968 – 1998, n = 420). Examination of the complete time-series (47 years) suggests relative stability in stock proportions since the late 1980s. Genetic estimates of stock composition were significantly associated with model-based estimates of returning MSW salmon (individual years r = 0.69, and overall mean r = 0.96). This work demonstrates that the analysis of both contemporary and archived samples in a mixed-stock context can disentangle levels of regional exploitation and directly inform assessment and conservation of Atlantic Salmon in the West Greenland interceptory Atlantic Salmon fishery.